1999
DOI: 10.1191/026921599666105472
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of patients with spinal cord injury: rehabilitation outcome study

Abstract: The results of this study provided more insight into the functional outcome of a group of patients with traumatic spinal cord injury. More research is needed to evaluate the rehabilitation programmes for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…These results are in accordance with those of other studies that found age was inversely related to functional status after SCI. 20,41 Many researchers 10,11,17 have shown a relation between lesion level and motor completeness of the lesion and functional outcome after inpatient rehabilitation. In the present study, we found that lesion level was significantly associated with the 3 scores of the Wheelchair Circuit.…”
Section: Relation Between Characteristics (Subject Lesion) Complicamentioning
confidence: 99%
See 3 more Smart Citations
“…These results are in accordance with those of other studies that found age was inversely related to functional status after SCI. 20,41 Many researchers 10,11,17 have shown a relation between lesion level and motor completeness of the lesion and functional outcome after inpatient rehabilitation. In the present study, we found that lesion level was significantly associated with the 3 scores of the Wheelchair Circuit.…”
Section: Relation Between Characteristics (Subject Lesion) Complicamentioning
confidence: 99%
“…Several researchers 8,17,[35][36][37][38][39] have studied changes in functional status during rehabilitation after SCI by using FIM scores or parameters of physical capacity as outcome variables. Most studies 8,17,35,36 only assessed subjects once or twice during their rehabilitation period (ie, at admission, and/or at the time of discharge from the rehabilitation center). Few studies have been published on the course of improvement during rehabilitation and few assess functional status at least 3 times during rehabilitation.…”
Section: Changes In Wheelchair Circuit Scoresmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 With regard to rolling, C5 tetraplegic patients have di culty, but C7 tetraplegic patients are much more capable. 3 Some C6 complete tetraplegics can roll, while some cannot.…”
Section: Introductionmentioning
confidence: 99%